Entrepreneurship as a Lifestyle: The role attitude plays in the employment dynamics of workers in the fitness and children's party sectors (Córdoba, Argentina) - Landa, Maria Ines (2019)
Within the framework of our research, the entrepreneur and variations on this concept emerged as a meaningful theme in the statements in interviews, and in the textual-digital material circulated in the recreation and entertainment spaces we surveyed. That is why this paper delves into the actions of the lifestyle through an analysis of the performances and practices of owners and workers in children's party venues and in fitness gyms. The paper's introduction offers a spatial-temporal contextualisation of the political and economic scenario in which the services covered by our case studies were supplied. We go on to present some conceptual plots that we attribute to the entrepreneurial lifestyle and then proceed to examine the cultural and historical dynamics through which these businesses were set up as places for bodily well-being (gyms) and fun (children's party salons) - both things we identify as catering to Argentina's Middle Class. While our approach stresses emerging patterns linking both cases, it also highlights the special factors shaping the symbolic features of each cultural scene. The similarities and differences found between the two cases revealed how a host of entrepreneurs (usually young people) was spawned. These youngsters need certain attitudes and creative skills to pursue their social and financial goals. Entrepreneurship as a lifestyle presupposes certain attitudes.